Burden and clustering of anaemia among children aged 6-59 months in Uttar Pradesh, India: a district-level spatial analysis - Sharma, Madhurima; Goswami, Indrajit (International Journal Of Community Medicine And Public Health, 2024)
Background: In the previous decade, India held the position of being the foremost contributor to childhood anemia among developing nations. In India, 89 million children aged 6-59 months suffer from anaemia. The study attempts to examine the spatial prevalence and detect the clustering of anaemia in Uttar Pradesh and also tries to identify the determinants of anaemia among children aged 6-59 months. Methods: The study utilized secondary data from the national family health survey-5 conducted in 2019-2021. It employed spatial analysis software, including ArcGIS 10.8 and GeoDa 1.22, incorporating Moran’s index. The assessment of factors predicting the prevalence of anemia among children involved the application of a logistic regression model using STATA-17, considering socio-economic, demographic, maternal, and child characteristics. Results: The anaemia prevalence is highest in Kanshiram Nagar and lowest in Allahabad districts. A total of 38 districts of Uttar Pradesh have more than national level average (67.1%-NFHS-5) of anaemia. Results also shows that 66.7% and 65.3% children 6-59 months age group were anaemic in urban and rural areas respectively. Around 70.7 % of children belonging to poorest wealth status and 69.4% of children who lived in rural areas were anaemic. Increase of mothers age, education, receipt of full ANC and richer wealth status reduce the risk of childhood anaemia. Conclusions: The correlation between anemia in preschool-aged children and various socioeconomic factors was significant. The research proposes directing efforts towards districts in Uttar Pradesh identified as hot-spots with a higher prevalence of anemia.